CD44 Promotes Inflammation and Extracellular Matrix Production During Arteriovenous Fistula Maturation - Kuwahara, Go (Arterioscler Thromb Vasc Biol, 2017)
OBJECTIVE: Arteriovenous fistulae (AVF) remain the optimal conduit for hemodialysis access but continue to demonstrate poor patency and poor rates of maturation. We hypothesized that CD44, a widely expressed cellular adhesion molecule that serves as a major receptor for extracellular matrix (ECM) components, promotes wall thickening and ECM deposition during AVF maturation. APPROACH AND RESULTS: AVF were created via needle puncture in wild-type (WT) C57BL/6J and CD44 knockout (KO) mice. CD44 mRNA and protein expression was increased in WT AVF. CD44 KO mice showed no increase in AVF wall thickness (8.9 μm vs. 26.8 μm; P = 0.0114), collagen density, and hyaluronic acid density, but similar elastin density when compared to control AVF. CD44 KO mice also showed no increase in VCAM-1 expression, ICAM-1 expression and MCP-1 expression in the AVF compared to controls; there were also no increased M2 macrophage markers (TGM2: 81.5 fold, P = 0.0015; IL-10: 7.6 fold, P = 0.0450) in CD44 KO mice. Delivery of MCP-1 to CD44 KO mice rescued the phenotype with thicker AVF walls (27.2 μm vs. 14.7 μm; P = 0.0306), increased collagen density (2.4 fold; P = 0.0432), and increased number of M2 macrophages (2.1 fold; P = 0.0335). CONCLUSIONS: CD44 promotes accumulation of M2 macrophages, ECM deposition and wall thickening during AVF maturation. These data show the association of M2 macrophages with wall thickening during AVF maturation and suggest that enhancing CD44 activity may be a strategy to increase AVF maturation.